2011
DOI: 10.1002/aenm.201100036
|View full text |Cite
|
Sign up to set email alerts
|

Halogenated Boron Subphthalocyanines as Light Harvesting Electron Acceptors in Organic Photovoltaics

Abstract: The fi eld of organic photovoltaics (OPVs) is attracting enormous interest due to its promise of providing a low-cost, easily processable technology for energy generation. Whilst the shortcircuit current density ( J SC ) of OPV devices can be optimized through morphology control, [ 1 ] intermixing, [ 2 , 3 ] nanostructuring [ 4 ] or templating [ 5 ] amongst other techniques, the opencircuit voltage ( V OC ) is critically dependent on the choice of photoactive materials. The relative abundance of suitable comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
169
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(175 citation statements)
references
References 28 publications
(15 reference statements)
4
169
0
2
Order By: Relevance
“…As an acceptor, we investigate the use of hexachlorinated boron subphthalocyanine chloride (Cl 6 SubPc, Figure 1 c). It was previously shown that SubPc/Cl 6 SubPc ( I G = 1.8 eV) increases the V oc compared to SubPc/C 60 ( I G = 1.3 eV), from V oc = 1.1 V to the remarkably high V oc = 1.3 V. [ 18 ] This resulted in an effi ciency of η p = 2.7%, for a fullerene-free solar cell. We here pair the acceptor material Cl 6 SubPc with SubNc.…”
Section: Introductionmentioning
confidence: 94%
“…As an acceptor, we investigate the use of hexachlorinated boron subphthalocyanine chloride (Cl 6 SubPc, Figure 1 c). It was previously shown that SubPc/Cl 6 SubPc ( I G = 1.8 eV) increases the V oc compared to SubPc/C 60 ( I G = 1.3 eV), from V oc = 1.1 V to the remarkably high V oc = 1.3 V. [ 18 ] This resulted in an effi ciency of η p = 2.7%, for a fullerene-free solar cell. We here pair the acceptor material Cl 6 SubPc with SubNc.…”
Section: Introductionmentioning
confidence: 94%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4 In general, BsubPcs hold significant promise as organic electronic materials, 18 having been demonstrate as both electron donors, 19 electron acceptors, [20][21] and ambipolar interlayers 22 in singlet fission free organic photovoltaic devices. BsubPcs have been used with the complimentary absorbers α-sexithophene and subnaphthalcyanine chloride (Cl-BsubNc) to construct a planar heterojunction photovoltaic cell that absorbed a broad portion of the visible spectrum that also featured an energy cascade (transferring excitons from Cl-BsubPc to ClBsubNc within the cell) leading to a power conversion efficiency of up to ~8 %.…”
mentioning
confidence: 99%
“…Alternatives to fullerenes for vacuum-deposited small-molecule organic solar cells mainly comprise perylene derivatives 4 or halogenated (sub-) phthalocyanines [16][17][18] . However, these non-fullerene acceptors rarely show improved performance over their fullerene counterparts.…”
mentioning
confidence: 99%